Selective killing of leukemia cells: Yamanaka factors' new trick. (20th March 2020) - Xie, Huafeng; Graf, Thomas
Abstract: The four transcription factors of the Yamanaka cocktail (Oct4, Sox2, Klf4, and Myc, termed OSKM) are famously capable of reprogramming somatic cells into induced pluripotent stem cells (iPSCs). In an article recently published in Nature Communications, Wang et al describe the unexpected discovery that short‐term activation of OSKM expression in acute myeloid leukemia cells in vivo induces apoptosis while negligibly affecting normal hematopoietic stem and progenitor cells (Nat Commun 2019;10:5594). These findings have potential implications for novel anticancer strategies. Abstract : Schematics of the experimental protocol used to demonstrate the selective anti‐tumor effect of the OSKM factors in vivo. Briefly, HSPCs from reprogrammable mice were isolated, infected in culture for 2 days with a retrovirus containing MLL‐AF9‐GFP and transplanted into sublethally irradiated mice. One week later the percentage of GFP+ cells in the bone marrow and blood was determined and animals treated with doxycycline (doxy) for 1 week to activate OSKM in the donor cells or left untreated (no doxy). The mice were then monitored for several months for the onset of leukemia and death. While untreated animals died within 20 days, most of the mice with transient OSKM activation survived for at least 1 year. MLL‐AF9‐infected HSPCs from reprogrammable mice were competitively repopulated with control HSPCs from reprogrammable mice and the recipients treated with doxy. This showed that the MLL‐AF9 cells died while the control HSPCs survived.